ANALISA KEGUNAAN DAN KEMUDAHAN LAYANAN MOBILE JKN PADA UPTD PUSKESMAS DEPOK DENGAN USE QUESTIONNAIRE DAN IPA - Rizal Nugraha; Lia Mazia; Lilyani Asri Utami (Universitas Teknokrat Indonesia, 2022)
Android applications are required to have quality and attractive appearance so that the information submitted can be received by users well in addition to attracting visitors to continue to access the android application. The features provided by the Android application must function properly according to its purpose, in addition to the ease and convenience of users in using or running the content in the Android application. All of these are aspects that are necessary in the development of an android application. The JKN Mobile Application is a form of digital transformation of the BPJS Health business model, which was originally in the form of administrative activities carried out at Branch Offices or Health Facilities, transformed into an application that can be used by participants anywhere at any time without time constraints (self service). Currently, there are> 1,000,000 users of the Android version of the JKN Mobile Application and the iOS version of the JKN Mobile Application of> 2,000 users. To find out whether the android application can be said to be of quality, it can be tested on everything in the android application. In testing the quality of the android application, the method used is the Use Questionnaire and Importance Performance Analysis (IPA) by using a questionnaire that is submitted to the specified respondents. Based on the gap analysis, it was found that Mobile JKN users at the UPTD Puskesmas Depok felt that the application still needed to be improved.